2018
DOI: 10.1155/2018/2385386
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Patients with Systemic Lupus Erythematosus in Malta: A Population Based Cohort Cross-Sectional Study

Abstract: Systemic Lupus Erythematosus (SLE) is a multisystemic autoimmune disorder. The aim of this study was to characterise the SLE patients living in Malta in order to estimate the prevalence and incidence of SLE and characterise the clinical presentation as well as identify any unmet needs. 107 SLE patients who fulfilled SLICC classification criteria were identified. These were invited to participate in the study by means of an interview, blood and urine tests, and filling of the following questionnaires: Fatigue S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Similar to this work, a study developed in Minas Gerais that evaluated the nutritional status and the level of physical activity in patients with SLE, found a higher prevalence of overweight (35.9%) and obesity (28.3%) [18]. Another study that characterized SLE patients residing in Malta, identified a prevalence of 31.5% of overweight and 29.3% of obesity [8].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar to this work, a study developed in Minas Gerais that evaluated the nutritional status and the level of physical activity in patients with SLE, found a higher prevalence of overweight (35.9%) and obesity (28.3%) [18]. Another study that characterized SLE patients residing in Malta, identified a prevalence of 31.5% of overweight and 29.3% of obesity [8].…”
Section: Discussionsupporting
confidence: 68%
“…In addition to sarcopenia, other changes in body composition can be detected and include abnormalities in nutritional status. An increase in the prevalence of overweight / obesity and a proportion, albeit lower, of malnutrition have been identified [8].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic, autoimmune and multisystem disease with a large spectrum of clinical manifestations including the joints. 1 Despite multiple body systems affected by this disease, with the improvement of diagnosis and treatment, patients live longer and as a result are more prone to developing musculoskeletal symptoms, which become the most common long-term complaints for this illness. It is reported that more than 90% of the SLE patients are affected by arthritis or arthralgia.…”
Section: Introductionmentioning
confidence: 99%
“…This systematic review followed the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline [ 30 ]. The review was registered with PROSPERO—the International Prospective Register of Systematic Reviews CRD: 42020197495.…”
Section: Methodsmentioning
confidence: 99%